2006
DOI: 10.1016/j.biocel.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan fragments activate nitric oxide synthase and the production of nitric oxide by articular chondrocytes

Abstract: Chondrocyte CD44 receptors anchor hyaluronan to the cell surface, enabling the assembly and retention of proteoglycan aggregates in the pericellular matrix. Hyaluronan-CD44 interactions also provide signaling important for maintaining cartilage homeostasis. Disruption of chondrocyte-hyaluronan contact alters CD44 occupancy, initiating alternative signaling cascades. Treatment with hyaluronan oligosaccharides is one approach to uncouple CD44 receptors from its native ligand, hyaluronan. In bovine articular chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…A wide range of activities can be explained by a large number of Ha-binding receptors such as cell surface glycoprotein CD44, the receptor for hyaluronic acid-mediated motility (RHAMM), and several other receptors possessing Ha-binding motifs, for example: transmembrane protein layilin, hyaluronic acid receptor for endocytosis (HARE), lymphatic vessel endocytic receptor (LYVE-1), and also intracellular HA-binding proteins including CDC37, RHAMM/IHABP, P-32, and IHABP4 (Underhill, 1992;Forsberg et al, 1994;Pohl et al, 2000;Pure and Cuff, 2001;Toole, 2001;Weigel et al, 2002;Hascall et al, 2004;Hajjaji et al, 2005;Nawrat et al, 2005;Hill et al, 2006;Iacob and Knudson, 2006). It has been shown that the HA level is elevated in various cancer cells (Lin and Stern, 2001) and it is believed to form a less dense matrix, thus enhancing the cell's motililty as well as invasive ability into other tissues (Hill et al, 2006).…”
Section: Carcinogenicitymentioning
confidence: 99%
“…A wide range of activities can be explained by a large number of Ha-binding receptors such as cell surface glycoprotein CD44, the receptor for hyaluronic acid-mediated motility (RHAMM), and several other receptors possessing Ha-binding motifs, for example: transmembrane protein layilin, hyaluronic acid receptor for endocytosis (HARE), lymphatic vessel endocytic receptor (LYVE-1), and also intracellular HA-binding proteins including CDC37, RHAMM/IHABP, P-32, and IHABP4 (Underhill, 1992;Forsberg et al, 1994;Pohl et al, 2000;Pure and Cuff, 2001;Toole, 2001;Weigel et al, 2002;Hascall et al, 2004;Hajjaji et al, 2005;Nawrat et al, 2005;Hill et al, 2006;Iacob and Knudson, 2006). It has been shown that the HA level is elevated in various cancer cells (Lin and Stern, 2001) and it is believed to form a less dense matrix, thus enhancing the cell's motililty as well as invasive ability into other tissues (Hill et al, 2006).…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Studies on activated macrophages have shown that HA fragments induce the expression of chemokines such as macrophage inflammatory protein-1a/b, RANTES and monocyte chemotactic protein-1, the functions of which are crucial in initiating and maintaining the inflammatory response [16]. Furthermore, expression of hyaluronan synthase-2, aggrecan, matrix metalloproteinase-3/13, and inducible nitric oxide synthase have been stimulated by small HA fragments in various types of chondrocytes [17,18]. Short HA fragments have been reported to promote cell proliferation of chondrocytes [18], endothelial cells and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In periodontal disease, PDL cell function is compromised as bacterial proteases destroy the integrity of the ECM and release fragmented adhesion molecules, including fibronectin fragments that induce apoptosis, into the inflammatory milieu. In addition, the degraded matrix molecules, like those from fibronectin and hyaluronan, may stimulate the resident cells around the sites of inflammation to produce proinflammatory cytokines and nitric oxide (6,28,30,31,34,56,67,76).…”
mentioning
confidence: 99%